Membangun Pesantren Melalui Pengembangan Sistem Pelaporan dan Strategi Pemasaran Digital - Mutiara Puspa Widyowati; Bayu Dwi Prasetyo; Chaidir (Rural Development For Economic Resilience (RUDENCE), 2021)
ABSTRACT The purpose of community service activities at the AL-Mahali Islamic Boarding School is to help overcome the obstacles faced by the pesantren, namely the weak reporting system and marketing media at the Al-Mahali Islamic Boarding School. Activities are carried out through three types of activities, namely transfer of knowledge about accounting and marketing concepts, assistance in preparing financial reports and making promotional media, as well as evaluating the results of activities. All activities have been carried out. The outputs in the form of a simple accounting system, Islamic boarding school accounting guidelines, and promotional media are expected to help the development of Islamic boarding schools. Good financial governance is expected to help make more accurate decisions and new strategies and promotional media are expected to increase the number of Islamic boarding school students.   ABSTRAK Tujuan dari kegiatan pengabdian kepada masyarakat pada Pesantren AL-Mahali adalah untuk membantu mengatasai kendala yang dihadapi pesantren, yaitu lemahnya sistem pelaporan dan media pemasaran pada Pesantren Al-Mahali. Kegiatan dilakukan melalui tiga jenis kegiatan, yaitu transfer ilmu mengenai konsep akuntansi dan pemasaran, pendampingan penyusunan laporan keuangan dan pembuatan media promosi, serta evaluasi hasil kegiatan. Seluruh kegiatan telah terlaksana. Hasil luaran berupa sistem akuntansi sederhana, pedoman akuntansi pesantren, dan media promosi diharapkan dapat membantu pengembangan pesantren. Tata kelola keuangan yang baik diharapkan dapat membantu pembuatan keputusan yang lebih akurat dan strategi serta media promosi yang baru diharapkan dapat meningkatkan jumlah santri pesantren.